Network management and remote monitoring via SMS application / Rozita Md. Ali - Md. Ali, Rozita (Faculty of Information Technology and Quantitative Sciences, 2006)
Nagios is an open source network monitoring tool. It is free, powerful and flexible. It can be tricky to learn and implement, but can reduce enormously the amount of time required to keep track of how your organization's IT infrastructure is performing. To understand the usefulness of Nagios, consider a typical IT infrastructure that one or more system administrators are responsible for. Even a small company may have a number of pieces of hardware with many services and software packages running on them. Larger companies may have hundreds or even thousands of items to keep up and running. Both small and large companies may have decentralized operations, implying a decentralized IT infrastructure, with no ability to physically see many of the machines at all.